Human capital in Chile: The development of numeracy during the last 250 years. Issue 3 (2nd September 2022) - Llorca-Jaña, Manuel; Rivas, Javier; Pérez, Ignacio; Navarrete-Montalvo, Juan
ABSTRACT: This paper studies the evolution of numeracy in Chile for cohorts born from the 1780s to the 1970s, providing a new series of this important indicator of human capital, essential to promote economic growth. This is the longest series currently available of any human capital indicator for Chile. It shows that numeracy was very low until the early twentieth century but that, contrary to traditional interpretations, it increased gradually from the 1780s (well before the promulgation of the primary instruction law of 1860), until full basic numeracy skills were achieved by the mid-twentieth century. This transition was completed some 3–4 decades after parallel developments occurred in the leading countries of the region and some 120 years behind the most developed areas of Europe. This development was characterized by high gender numeracy inequality until the first decades of the twentieth century, as well as by a pronounced regional inequality. However, there was a quick process of convergence across provinces, completed at the same time as gender inequality was reduced. Our numeracy data is also consistent with alternative human capital indicators such as literacy and schooling, and we provide a set of explanations about why they all improved, and their timing.